2017
DOI: 10.1186/s13068-017-0816-y
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale steam explosion pretreatment with 2-naphthol to overcome high softwood recalcitrance

Abstract: BackgroundSteam explosion pretreatment has been examined in many studies for enhancing the enzymatic digestibility of lignocellulosic biomass and is currently the most common pretreatment method in commercial biorefineries. It is however not effective for overcoming the extremely high recalcitrance of softwood to biochemical conversion. Recent fundamental research in small-scale liquid hot water pretreatment has shown, though, that the addition of a carbocation scavenger like 2-naphthol can prevent lignin repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 41 publications
5
37
0
Order By: Relevance
“…7. In accordance with previous works [8,13] it is observed that the addition of a carbonium scavenger such as 2naphthol (1) allowed a better lignin extractability during the washing step with ethanol, (2) strongly decreased the formation of Hibbert's ketones in SEL3N and SEL4N (S/S' = 13.4 and 16.6 respectively, Table 1). In acid conditions (SEL6-9) the lower S/S' values observed (S/S' = 6.2-2.7) are in accordance with an acid-catalyzed hydrolytic route producing Hibbert's ketones.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…7. In accordance with previous works [8,13] it is observed that the addition of a carbonium scavenger such as 2naphthol (1) allowed a better lignin extractability during the washing step with ethanol, (2) strongly decreased the formation of Hibbert's ketones in SEL3N and SEL4N (S/S' = 13.4 and 16.6 respectively, Table 1). In acid conditions (SEL6-9) the lower S/S' values observed (S/S' = 6.2-2.7) are in accordance with an acid-catalyzed hydrolytic route producing Hibbert's ketones.…”
Section: Discussionsupporting
confidence: 91%
“…As seen in Table 1 and Fig. 2 and in accordance with previous reports [3,8,13], the presence of naphthol significantly increased the delignification yields.…”
Section: Lignin Yieldssupporting
confidence: 91%
See 1 more Smart Citation
“…Steam explosion pretreatment does not involve the use of chemicals, which is an advantage compared to other pre-treatments. Therefore, steam explosion pre-treatment of biomass prior to pelletisation can increase heating value, bonding properties and hydrophobicity of the wood [2,[156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175] .…”
Section: Steam Explosionmentioning
confidence: 99%
“…In fact, there are number of pretreatment technologies that exist; however, only a few processes match industry norms. Table presents some pilot‐scale studies on LB pretreatment that conform to industrially relevant parameters . Technology scouting enabled the best technology suited to particular LB and the conditions of production facility to be located.…”
Section: Review On the Current Progress Of 2g‐ethanol Production At Cmentioning
confidence: 99%